Constraining the duty cycle of transient low-mass X-ray binaries through simulations. Issue 2 (20th June 2019) - Carbone, D; Wijnands, R
Abstract: We performed simulations of a large number of so-called very faint X-ray transient sources from surveys obtained using the X-ray telescope aboard the Neil Gehrels Swift Observatory on two Galactic globular clusters, and the Galactic Centre. We calculated the ratio between the duty cycle (DC) we input in our simulations and the one we measure after the simulations. We found that fluctuations in outburst duration and recurrence times affect our estimation of the DC more than non-detected outbursts. This biases our measures to overestimate the simulated DC of sources. Moreover, we determined that compact surveys are necessary to detect outbursts with short duration because they could fall in gaps between observations, if such gaps are longer than their duration. On the other hand, long surveys are necessary to detect sources with low DC because the smallest DC a survey can observe is given by the ratio between the shortest outburst duration and the total length of the survey. If one has a limited amount of observing time, these two effects are competing, and a compromise is required which is set by the goals of the proposed survey. We have also performed simulations with several artificial survey strategies in order to evaluate the optimal observing campaign aimed at detecting transients as well as at having the most accurate estimates of the DC. As expected, the best campaign would be a regular and dense monitoring that extends for a very long period. The closest real example of such a data set is the monitoring of the Galactic Centre.